Selectively Nucleated Lateral Crystallization for a Large Single-Grained Pb(Zr, Ti)O3 on Polycrystalline-Silicon Thin-Film Transistors for System-On-Glass Applications. Issue 1792 (16th June 2015) - Park, Jae Hyo; Joo, Seung Ki
ABSTRACT: A single-grained Pb(Zr, Ti)O3 (PZT) was successfully grown for the gate dielectric of polycrystalline-silicon (poly-Si) thin-film transistor (TFT). The total structure was MoW/PZT/HfO2 /poly-Si/glass. The giant single-grained PZT was obtained by controlling the artificial nucleation formed by Pt dots in a desirable location and enlarging the nucleated seed until it covers the poly-Si channel. The single-grained diameter size was 40 μm with a (100) dominated texture. The poly-Si memory device with single-grained PZT showed an excellent ferroelectric, electrical and reliability properties comparing with poly-Si memory device with poly-grained PZT. Moreover, eliminating the grain boundary in PZT film showed the fatigue and retention characteristics with only 1.1 % after 10 13 cycles and 22 % after 1 month, respectively.